THE NUTRITIONAL PROFILE OF BEEF AND ITS IMPLICATIONS FOR DIETARY HEALTH - Abdullah Omar A Alshuqair, Yasser Ali A Almotawa, Muqbil Hamoud Muqbil Alotaibi, Thamer Sulaiman Alghofaili, Khaleel Abdulrahman Abdullah Alshamasi, Abdullah Ali Almohanna, Mohammad salem Almaqattar, Asem Abdulaziz A Alasem, Hana Ali Hamedi Alenzi,,; Khalid Mahdi Bin Mohammed Refaei, Meshari Suliman Hamad Almihbash, Wafaa Abdelsayed Abdullah Bamasoud, Bandar Saleh Ammash Almutairi, Maram Ibrahim Alnutayfi, Ahmed Hamad Tumahyi, Yahya Abdullah Tumayhi, (Chelonian Research Foundation, 2022)
Beef, a widely consumed red meat, is a significant source of essential nutrients in the human diet. This review examines the nutritional composition of beef and its potential role in promoting overall health when consumed as part of a balanced dietary regimen. The analysis considers the macronutrient profile, including protein, fat, and micronutrient content, such as iron, zinc, and vitamins. The review also explores the potential health benefits and risks associated with beef consumption, addressing factors like saturated fat, cholesterol, and the growing body of evidence regarding the relationship between red meat intake and chronic disease risk. Strategies for incorporating beef into a healthy, sustainable diet are discussed, with a focus on portion control, cooking methods, and the inclusion of lean cuts. This comprehensive assessment aims to provide a nuanced understanding of the nutritional value and dietary implications of beef, guiding health professionals and consumers in making informed choices regarding the role of red meat in a balanced, health-promoting diet. Keywords: Beef, red meat, nutrition, macronutrients, micronutrients, chronic disease, dietary recommendations